High Lithium Storage Performance of Mn-doped Sn4P3 nanoparticles. (20th August 2016) - Liu, Shuling; Zhang, Hongzhe; Xu, Liqiang; Ma, Lanbing; Hou, Xuan
Graphical abstract: The cycling performances with different current density: (a) 100 mA g −1 (b) 200 mA g −1 . Highlights: Mn-doped Sn4 P3 particles were synthesized via a facile ultrasonic assisted method. The Mn dopant content play crucial roles on structure stability of Sn-Mn-P structure. The Mn-doped Sn4 P3 has a potential application as anode material for Li-ion batteries. Abstract: This paper reports the synthesis of various molar concentrations of manganese (Mn)-doped Sn4 P3 nanoparticles and and their efficient use as anode materials for rechargeable lithium-ion batteries (LIBs). The nanoparticles were synthesized via a novel and facile ultrasonic assisted hydrothermal method and characterized in detail by various analytical techniques. The XRD, SEM, and TEM results showed that Mn ion was successfully substituted on the Sn4 P3 layered structure without any structure changes. The long cycle stability of the as-prepared Mn-doped Sn4 P3 nanoparticles have been tested as an anode material for lithium ion batteries at the different current density. By detailed experimental results exhibited that the Mn dopant content crucially determines the electrochemical performances of Sn4 P3 nanoparticles. Electrochemical measurements show that the Sn4 P3 nanoparticles with 0.10 mol% molar concentration of Mn dopant give the best cycling performances. They deliver a discharge capacity of 488 mAh g −1 after 150 cycles at the current density of 100 mA g −1 . Even after 150 cycles at a current density of 200 mA g −1, the specific capacity still could be remained at 420 mAh g −1 . Further increasing the current density to 1000 mA g −1, it could still maintain 255 mAh g −1 after 200 cycles. It is confirmed that Mn substitution in the Sn-Mn-P structure is an important pole to improve the structure stability and electrochemical properties.